2014
DOI: 10.3109/14767058.2014.892921
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of fat soluble antioxidants with gestational diabetes in Iran: a case–control study

Abstract: The level of retinol in the diabetic pregnant women was significantly lower than that in the control group. This reduction may be due to the reduced antioxidant defences in women with GDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…The altered antioxidant system is also observed and persists with age in the macrosomic rat and human newborns that became obese adults [ 27 , 46 ]. These observations are recently supported by several investigators who have observed increased oxidative stress in gestational diabetic women and animals [ 55 58 ] and their infants [ 59 ] and rat adult offspring [ 60 ]. In fact, our findings suggest that there is an increased oxidative stress in diabetic pregnant women and rats and their adult obese offspring that were macrosomic as newborns [ 27 , 46 ], in agreement with the results of previous studies [ 61 64 ].…”
Section: Major Metabolic Complications During Gestational Diabetessupporting
confidence: 57%
“…The altered antioxidant system is also observed and persists with age in the macrosomic rat and human newborns that became obese adults [ 27 , 46 ]. These observations are recently supported by several investigators who have observed increased oxidative stress in gestational diabetic women and animals [ 55 58 ] and their infants [ 59 ] and rat adult offspring [ 60 ]. In fact, our findings suggest that there is an increased oxidative stress in diabetic pregnant women and rats and their adult obese offspring that were macrosomic as newborns [ 27 , 46 ], in agreement with the results of previous studies [ 61 64 ].…”
Section: Major Metabolic Complications During Gestational Diabetessupporting
confidence: 57%
“…Among diabetic pregnancies, the adipokine RBP does not have a statistically significant association with the occurrence of PE ( 92 ). Other studies have investigated the association between higher RBP concentrations and the risk of gestational diabetes, finding both positive ( 93–96 ) and negative associations ( 97 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we found a negative association between GDM and serum levels of vitamin A at 24 weeks of gestation. Previous studies reported that GDM pregnant women may have lower vitamin A and E levels and suggest that this could be due to the increased oxidative status found under this condition as compared to healthy pregnancies [1619]. However, maternal supplementation with vitamin C/E in type 1 diabetes failed to increase cord or placental levels of these vitamins and it had no effect on placental markers of oxidative stress, activity of antioxidant enzymes, or lipid peroxidation markers [44].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis showed that maternal serum vitamin E level is significantly lower in pregnant women with gestational diabetes mellitus (GDM) as compared to healthy ones [16]. GDM has also been associated with low vitamin A status during pregnancy [17][18][19]. Supplementation with omega-3 fatty acids in combination with vitamin D or E can alleviate maternal oxidative stress in women with GDM or prediabetes [20] while there is no information on its effect on cord antioxidant status.…”
Section: Introductionmentioning
confidence: 99%